Study of the Effect of Manganese on The Structural and Optical Properties of Sno2 Membranes - Abbas Zuwid Khalaf; Qassem Hammadi Mahmoud (South Eastern European Journal of Public Health, 2024)
The effect of manganese addition on precipitated tin dioxide on quartz was studied using the pulsed laser method if the X-ray diffraction results showed that the pure tin oxide membrane has a polycrystalline structure and a quaternary phase, with growth in the crystalline directions (110), (101), (200), and (211) and the predominant ones were (101). Using a high-benefit electron scanning microscope (FE-SEM), the results showed that the addition of manganese smearing in small proportions significantly affected the surface nature and grain size, as the surface uniformity and grain size increased with increasing the percentage of distortion. Through optical examinations through the permeability spectrum of thin films of pure and tinged tin oxide, a gradual increase in permeability with an increase in the concentration of impurities, reaching high values ranging between 80-90%. As for the energy gap, the energy gap for manganese-inlaid membranes has been increased from 3.33 eV for the pure membrane to 3.57 eV. The sensing properties of these membranes were studied as a function of time at temperatures between 50-200 °C .